PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN MENGGUNAKAN APLIKASI KINEMASTER PADA SUBTEMA 2 PERUBAHAN ENEGI PADA SISWA KELAS III SD NEGERI 1 BONO TULUNGAGUNG - Anggi Rahma Wati; Ria Fajrin Rizqy Ana (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2023)
This research is motivated by the learning process in the classroom which is still dominated by listening to the teacher's explanation and using pictures. This makes students feel bored so that students' enthusiasm for learning is lacking. This study aims to develop, test the validity, and applicability of learning video media development products using the kinemaster application on subtheme 2 energy changes for third grade students of SD Negeri 1 Bono. This research uses a method with the ADDIE model which consists of the stages of analysis, design, development, implementation, evaluation. The data collection technique was carried out by testing the validity of the media, material and distributing questionnaires. The instruments used in this study used media expert validation sheets, material experts, and student questionnaires. The results obtained by the media validation by the validator obtained a percentage of 90% with a very valid category, the material validator assessment obtained a percentage of 92.5% with a very valid category, and the student response assessment obtained a percentage of 92% with a very valid category. Thus the results of this study can be concluded that